The online classroom : resources for effective middle level virtual education - Eisenbach, Brooke; Greathouse, Paula (Handbook of resources in middle level education., 2018)
"Researchers estimate that more than 2 million K-12 students were enrolled in some form of online school, district, or state virtual course over the 2015-2016 school year (Evergreen Education Group, 2015). Today's middle level learners are logging into virtual classrooms at a rapidly growing rate. As of 2015, middle level students represent 14% of learners taking virtual courses to supplement their current coursework, and 28% of full-time virtual school students. As a result, it is essential that teachers identify the unique needs of today's virtual middle level students and find ways to address these needs within this digital context. This book volume will explore resources centered on the growing world of virtual education and its implications for the middle level learner, middle level classroom, and middle level educator. It is our aim to provide virtual teachers and teacher educators the tools and information necessary to address the needs of middle level learners within blended or virtual classrooms. We invite researchers and teachers to share tips, strategies, guidance, and stories in working with middle level students in a blended, hybrid, or fully-online classroom setting"--